A Systematic Review on the Prevalence of Soil-Transmitted Helminth (STH) Infection from Cats and Dogs in Asia - Padua, Mark F F E. (Asian Journal of Biological and Life Sciences)
Aim/Background: Parasitic infections from both cats and dogs are considered a recurring problem in several developing countries. This review intends to provide the current cases, through published articles in various scholarly databases, the current prevalence of STH infection in dogs and cats. Materials and Methods: Isolation and epidemiological studies that focus on isolation of dog and cat intestinal parasites between 2010 and 2020 in Asia were searched systematically in PubMed, Research Gate, Google Scholar, and Science Direct databases, 106 articles are considered in this study, coming from 21 Asian countries. Results: A total of 106 articles are considered in this study coming from 21 Asian countries and initial analysis of qualified articles revealed 5, 028 documented isolated STH in dogs and cats with Ancylostoma caninum (1291; 25.7%) having the highest prevalence infecting dogs followed by Toxocara canis (999; 19.9%), while A. ceylenicum (12; 0.2%) and Ascarid worms (32; 0.6%) had low report isolations. Conclusion: Both hookworm and Toxocara infection in humans are considered public health concerns and their impact does not only include individual health but also the socio-economic impacts of the worm burden are undeniable. Until the time that effective prevention and therapeutic intervention has been implemented, surveillance studies for this neglected parasitic infection should be focused by both researchers and clinicians.
Keywords: Ancylostoma caninum; Ancylostoma duodenale; Asia; hookworms; Toxocara